Effect of Right Issue Announcement on Abnormal Return and Stock Trading Volume (Case Study on Companies Listed on the Indonesia Stock Exchange) - Moch. Kukuh Widyatmoko; A. Yusuf Imam Suja’i; Agus Salim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Right issue is an event that’s related to information’s publication as an announcement and can be used to observe the market reaction. Theoretically, the market reaction is measured by abnormal return and trading volume activity. This research used paired sample t-test to examine the effect of right issue’s announcement to the abnormal return and trading volume activity, using samples as much as 38 firms from 2017 to 2020. The observation period was 5 days before and 5 days after the announcement’s period. The result showed that the right issue’s announcement did not affect significantly to the abnormal return of firms, while affected significantly to the trading volume activity.